Invasive species - Helal, Marwa ca. 20. Jh (Nightboat Books, 2019)
A vernacular debut that uncompromisingly journeys towards its sole destination: the decolonization of the imagination.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Electronic books